The physiological functions and pharmaceutical applications of inulin: A review. (15th October 2020) - Wan, Xinhuan; Guo, Hao; Liang, Yiyu; Zhou, Changzheng; Liu, Zihao; Li, Kunwei; Niu, Fengju; Zhai, Xin; Wang, Lizhu
Highlights: Inulin, a fructan-type plant polysaccharide with average MW 5600−6300 g mol −1 . Inulin has functions of prebiotics, antioxidant, reglualting lipid metabolism, etc. Inulin can be a carrier for colon/tumor-targeting drug delivery. Abstract: Inulin (IN), a fructan-type plant polysaccharide, is widely found in nature. The major plant sources of IN include chicory, Jerusalem artichoke, dahlia etc. Studies have found that IN possessed a wide array of biological activities, e.g. as a prebiotic to improve the intestinal microbe environment, regulating blood sugar, regulating blood lipids, antioxidant, anticancer, immune regulation and so on. Currently, IN is widely used in the food and pharmaceutical industries. IN can be used as thickener, fat replacer, sweetener and water retaining agent in the food industry. IN also can be applied in the pharmaceutics as stabilizer, drug carrier, and auxiliary therapeutic agent for certain diseases such as constipation and diabetes. This paper reviews the physiological functions of IN and its applications in the field of pharmaceutics, analyzes its present research status and future research direction. This review will serve as a one-in-all resource for the researchers who are interested to work on IN.